2020
DOI: 10.3390/v12121440
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs as Potential Biomarkers for Viral Hepatitis B and C

Abstract: Around 257 million people are living with hepatitis B virus (HBV) chronic infection and 71 million with hepatitis C virus (HCV) chronic infection. Both HBV and HCV infections can lead to liver complications such as cirrhosis and hepatocellular carcinoma (HCC). To take care of these chronically infected patients, one strategy is to diagnose the early stage of fibrosis in order to treat them as soon as possible to decrease the risk of HCC development. microRNAs (or miRNAs) are small non-coding RNAs which regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 99 publications
1
38
0
1
Order By: Relevance
“…Future studies with more diverse and larger patient populations should reconcile the few discrepancies observed among various biomarker correlations and help solidify treatment stopping rules and predictive cutoff values. Measurement and analysis of novel HBV biomarkers will be complemented by the array of host markers that are being investigated to better monitor disease phase, including host genetic markers, micro-RNAs, as well as serum inflammatory and immune markers and cytokines [ 160 , 161 , 162 ]. These markers can be non-invasively measured and so extend the suite of tools for CHB disease activity interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies with more diverse and larger patient populations should reconcile the few discrepancies observed among various biomarker correlations and help solidify treatment stopping rules and predictive cutoff values. Measurement and analysis of novel HBV biomarkers will be complemented by the array of host markers that are being investigated to better monitor disease phase, including host genetic markers, micro-RNAs, as well as serum inflammatory and immune markers and cytokines [ 160 , 161 , 162 ]. These markers can be non-invasively measured and so extend the suite of tools for CHB disease activity interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…These markers can be non-invasively measured and so extend the suite of tools for CHB disease activity interpretation. Genetic markers (single nucleotide polymorphisms) have been associated with the risk of developing cirrhosis, fibrosis or HCC [ 160 ], while host miRNA regulation can indicate the development of fibrosis or HCC [ 161 , 163 ]. Additionally, certain cytokines have been observed to correlate with severity of HBV disease and clinical outcomes [ 162 , 164 , 165 , 166 , 167 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growth and development of the SMG is carried out under epithelial-mesenchymal interactions (Wang and Laurie, 2004 ), which are regulated by a complex of signaling molecules, including growth or differentiation factors, cell receptors and extracellular matrix (ECM) proteins. Activation of hepatic stellate cells, exaggerated expression of profibrogenic genes, and/or suppression of antifibrogenic genes can cause excessive and persistent accumulation of the ECM, which further leads to fibrosis (Wynn, 2008 ; Loureiro et al, 2020 ). This indicates that the target genes of the DE miRNAs in clusters 1 and 2 may be related to the growth and development of SMG ECM proteins and that their abnormal expression can cause infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM35 is a proapototic protein and can inhibit the Warburg effect, whereas RAN is involved in nucleocytoplasmic transport, but also in metastasis. HBV-miR-3 enhances cell invasion and proliferation by e.g., silencing PP1A and PTEN [ 255 , 256 ].…”
Section: Oncoviruses and Micrornamentioning
confidence: 99%
“…Several studies showed a role for HBx in up- and downregulating the expression of cellular microRNAs, including miR-10, miR-132, miR-143, and miR-193b. This has been the topic of excellent reviews [ 190 , 255 , 257 , 263 , 291 , 292 ]. HBx modulates microRNA expression by inducing epigenetic changes in microRNA-encoding genes or modulating expression of genes whose products are involved in microRNA biogenesis.…”
Section: Oncoviruses and Micrornamentioning
confidence: 99%